Pengaruh marketing mix dan customer bonding terhadap loyalitas pelanggan - Setiawan, Fran; Hermina, Nurul (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
This study aimed to investigate the connection between marketing strategy and customer loyalty for GoFood in Bandung. Quantitative techniques are used in this study. Meanwhile, a multiple linear regression analysis approach is used, with calculations performed with the aid of the SPSS version 25.0 application. It may be inferred from the reviewed literature and discussions that the Marketing Mix and Customer Bonding significantly affect the customer loyalty variable. This study's value lies in the fact that it provides new information that can be used to finish the project. and share your thoughts, ideas, and facts with PT. Gojek Indonesia keeps up the high level of service it has always provided and keeps working to increase client happiness and loyalty. This research shows that Customer Bonding and the Marketing Mix together have a substantial impact on customer loyalty at Gofood.